Oral administration of Bacillus coagulans TQ-35 alleviates allergic responses in OVA-sensitive BALB/c mice - Yifan Wang; Shanjun Chen; Chong Wang; Yi Zhang; Hongliang Zeng; Linglin Fu; Yanbo Wang (Food Science and Human Wellness)
Bacillus coagulans has been extensively studied so far, but there has been a lack of research on its usage in allergy. In this study, we designed to assess the effect of different concentrations of B. coagulans on food allergy in a BALB/c mouse model of ovalbumin (OVA)-induced food allergy and its effect on gut microbes. The assessment of symptoms, specific immunoglobulin E (IgE), T-cell differentiation, and related gene expression levels in sensitized mice by assay indicated that high doses of oral B. coagulans could alleviate allergic symptoms. Treatment with B. coagulans, in the high-dose group, signif icantly reduced IgE and IgG1 levels and modulated the balance of T helper type 1 cell (Th1) and Th2 and the expression of relevant genes in the spleen. 16S rRNA analysis showed that probiotics improved the structure of the microbiota, in particular by boosting the percentage of Clostridia, Bacteroides vulgatus and Enterococcus faecium, and by increasing the abundance of microbial species, thereby modulating the immune system. Therefore, this study can provide insights into the practical application of B. coagulans doses to alleviate OVA allergy.